Mitos Keberlanjutan sebagai Legitimasi: Analisis Semiotik Barthes atas Praktik Conspicuous Sustainability di Ruang Publik Perkotaan Jakarta - Gita Mahyarani; Endang Susilomurti (Journal of Creative Student Research, 2026)
This study analyzes green consumption practices through the use of dedicated electric vehicle (EV) parking spaces in Jakarta’s public spaces as a form of conspicuous sustainability. Using Roland Barthes’ semiotic approach, the research examines how visual signs and spatial arrangements in shopping malls (Pondok Indah Mall and Kota Kasablanka) and government offices (Ditjen Minerba and Cyber 2 Building Kuningan) produce social and moral meanings. Data were collected through non-participant observation and visual documentation at these four sites, followed by analysis using Barthes’ three levels of meaning (denotation, connotation, and myth). The analysis employs Barthes’ three levels of meaning: denotation, connotation, and myth. Findings indicate that EV parking functions not only as a functional facility but as a symbolic communication medium that converts green values into symbolic capital. Through mechanisms of denotative privileged access, connotative social status, and the myth of "green as universal virtue," conspicuous consumption practices transform into conspicuous sustainability—morally legitimized status consumption. This article contributes to environmental communication studies by integrating Barthesian semiotics and conspicuous consumption theory to unpack the ambivalence of sustainability discourse in urban Indonesia.